Subverting the empire: exploration in contemporary Australian fiction - Genoni, Paul (Australia Research Institute at Curtin University of Technology., 2001)
This paper examines the way in which contemporary Australian novelists use various tropes derived from exploration in order to embellish themes of personal search in their fiction. By doing so they have borrowed from the language and myths created by what was essentially an exercise in imperialism, and applied them to the quest by individuals in the settler society to find a permanent spiritual home in the new country. The exploration imagery proves to be apposite, in that just as the empire's hopes were dashed when exploration of the inland was repelled by the barren heart of the continent, so too has the metaphysical exploration of the same spaces foundered on uncompromising and withholding landscapes.